The Effect Of Temperature And Humidity On Banana Sale Products In Various Types Of Packaging With Long Storage Time - Aprilandani, Sinta; Tanggasari, Devi (Protech Biosystems Journal, 2022)
The drying process carried out in making banana sale will cause the moisture content in banana sale with various types of banana packaging is very influential, the storage of banana sale has decreased quality in terms of temperature, humidity and moisture content. The purpose of this study was to determine the effect of packaging method using (opp plastic, vacuum and jar) and storage duration on temperature, humidity and moisture content of banana sale. This study consisted of one factor, namely packaging using opp plastic, packaging using vacuum and packaging using jars. Duration of storage with 15 observations for 1 month every 2 days 1 observation (2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, and 30) in a refrigerator temperature around 7˚C. Therefore, a method is needed to maintain the quality of banana sale during storage by applying packaging technology. Data were processed using a completely randomised design (CRD). Factorial with three repetitions, the parameters analysed were the effect of temperature, humidity and moisture content. The results showed that the storage of banana sale with various types of packaging for 1 month gave the best results on the use of packaging using vacuum type for the best storage for 1 month compared to the use of packaging types using opp plastic and jars.